Clinical outcomes of left main coronary artery disease patients undergoing three different revascularization approaches. Issue 7 (February 2018) - Su, Chieh-Shou; Chen, Yu-Wei; Shen, Ching-Hui; Liu, Tsun-Jui; Chang, Yen; Lee, Wen-Lieng
Abstract : Abstract: Significant unprotected left main (LM) coronary artery disease is frequently associated with severe multivessel disease and increased mortality and morbidity compared with non-LM coronary artery disease. This study compared the clinical outcomes of patients with LM disease who received percutaneous coronary intervention (PCI) with stenting, conventional coronary-artery bypass grafting (C-CABG), and robot-assisted CABG (R-CABG). This retrospective study analyzed 472 consecutive LM disease patients who underwent three different revascularization approaches at a tertiary medical center between January 2005 and November 2013. Of the 472 LM disease patients, 139 received R-CABG, 147 received C-CABG, and 186 received PCI. The need for target vessel revascularization (TVR) was highest in the PCI group. The R-CABG group had significantly lower rates of in-hospital and follow-up all-cause deaths compared with the other 2 groups (1.4% vs. 3.4% and 9.7%, P = .0058; 13.7% vs. 29.3% and 29.6%, P = .0023, respectively). Patients in the R-CABG group had significantly lower rates of intra-aortic balloon pump assistance, and shorter duration of ICU and total hospital stay compared to patients in the C-CABG group. However, revascularization modality, SYNTAX scores, and residual SYNTAX scores were not independent predictors of in-hospital or long-term mortality. In this cohort of LM disease patients treated at a tertiary medical center, PCI is a reasonable choice in patients with less lesion complexity but who are older and have comorbidities. R-CABG is feasible in stable LM disease patients with high SYNTAX scores, and is an effective alternative to C-CABG in LM disease patients with few risk factors. However, revascularization modality per se was not a determinant for long-term mortality in our real-world practice.